A new record of late Ediacaran acritarchs from La providencia group (Tandilia System, Argentina) and its biostratigraphical significance - Julia Arrouy, Maria; Gaucher, Claudio; Poire, Daniel G.; Xiao, Shuhai; Gomez Peral, Lucia E.; Warren, Lucas V. [UNESP]; Bykova, Natalia; Quaglio, Fernanda (Elsevier B.V., 2019)
A well preserved assemblage of organic-walled microfossils is described from the Alicia and Cerro Negro formations of the La Providencia Group. The microbiota is dominated by Leiosphaeridia species (L. minutissima, L. tenuissima, L. crassa and L. jacutica) and comprises colonial sphaeroids (Synsphaeridium sp.) and filamentous microfossils of the genus Siphonophycus. The assemblage is assigned to the Late Ediacaran Leiosphere Palynoflora (LELP), which is consistent with the occurrence of the discoidal fossil Aspidella (< 565 Ma) in the overlying unit. The distribution of microfossils within the Alicia Formation is mainly controlled by the shallowing upward trend and thus, environmental factors. This is indicated by the abundance and size of filaments, which tend to occur near to the paleoshore in shallow water settings. Furthermore, large leiospheres also occur in shallower facies together with filaments, in accordance with existing models for acritarch ecology and distribution in the Proterozoic marine successions. The absence of acanthomorphic acritarchs is thus interpreted as a real evolutionary trend, and not as a result of preservational or environmental biases. Regarding the preservation of microfossils, a higher Thermal Alteration Index for the Alicia Formation, compared with older and younger units, is interpreted as a result of hydrothermal overprint and/or contact metamorphism by basic dikes.